HUBUNGAN PEMBERIAN MAKANAN PENDAMPING ASI (MP-ASI) DAN SANITASI RUMAH DENGAN STATUS GIZI BAYI KELUARGA MISKIN PERKOTAAN - Bella Hayyu Risky Herlistia; Lailatul Muniroh (Universitas Airlangga, 2015)
Infants is one of the most vulnerable group to nutritional problems. One of the immediate cause of nutritional problem in infants is improper complementary feeding and one of the underlying cause is household sanitation. Proper complementary feeding and good household sanitation are difficult to be fulfilled by poor families. This research aims to analyze the relationship between complementary feeding and household sanitation with infants’ nutritional status in urban poor families. This was a cross sectional research with total sample of 58 infants aged 6-12 months from poor households who were registered in integrated health post (Posyandu) in Gunung Anyar, Surabaya Public Health Center and randomly selected by using simple random sampling technique. Complementery feeding data was collected using questionnaire through interview, while household sanitation was determined by observation. Body weight and body length were measured using baby scale and length board. The data was analyzed statically using chi-square test. The result showed the majority of complementary feeding practice and household sanitation among urban poor families were categorized as good. Statistic test showed that there was no relationship between complementary feeding and infants’ nutritional status (p=0,259). In contrast, result found there was an association between household sanitation (p=0,031) and infants’ nutritional status in urban poor families. The conclusion of this study is that good household sanitation contribute more to infants’ nutritional status than complementary feeding. It is necessary for poor family to improve household sanitation and optimize infant’s feeding practice with varied food and healthy snack.Keywords: complementary feeding, infants, nutritional status poor family, sanitation